Modification of poly(styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene) via free‐radical grafting and its photo‐crosslinking. Issue 12 (15th October 2021) - Harlay, Agnès; Brossier, Thomas; Morand, Nicolas; Batistella, Marcos; Regazzi, Arnaud; Blanquer, Sébastien; Lopez‐Cuesta, José; Robin, Jean‐Jacques
Abstract: Poly(styrene‐ b ‐(ethylene‐ co ‐butylene)‐ b ‐styrene) (SEBS) is functionalized via radical grafting with 4‐vinyl‐1‐cyclohexene 1, 2‐epoxide (VCHO) initiated using 2, 5‐Bis(tert‐butylperoxy)‐2, 5‐dimethylhexane. The existence of the epoxide group on the SEBS backbone is evidenced by 1 H nuclear magnetic resonance. A size exclusion chromatography (SEC) study reveals some chain coupling, and this phenomenon is limited by controlling the quantities of peroxide and monomer reagents used during the radical grafting. Photo‐crosslinking of SEBS‐ g ‐VCHO under ultraviolet irradiation in the presence of a cationic initiator is then successfully performed with resultant gel contents higher than 85%. Mechanical properties of SEBS and crosslinked materials are measured by tensile tests on thin films. On the one hand, those tests reveal a significant increase of Young's modulus of the crosslinked materials. On the other hand, the diminution of elongation at break is much more limited; crosslinked materials retain their elastomeric properties with an elongation at break greater than 200%. Finally, the photosensitive SEBS‐ g ‐VCHO is used to show the adhesion performance of the photo‐crosslinking coating as well as a resin for the stereolithography process. Abstract :